2022
DOI: 10.1016/j.medcli.2021.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Exercise Testing in Patients with Post-COVID-19 Syndrome

Abstract: Antecedentes y objetivo: Varios informes han demostrado la persistencia de síntomas a largo plazo luego de la infección inicial por COVID-19 (síndrome post-COVID-19). El objetivo de este estudio fue analizar las características de la prueba de esfuerzo cardiopulmonar (PECP) realizada en pacientes con antecedentes de infección por COVID-19, comparando sujetos según la presencia de síndrome post-COVID-19. Métodos: se realizó un estudio transversal. Se incluyeron pacientes consecutivos > 18 años con an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 23 publications
5
31
0
3
Order By: Relevance
“…Our study is consistent with six studies that have reported lower peak VO2 among those with PASC compared to recovered individuals at 3-6 months after COVID-19. [19][20][21][22][23][24] Our findings build upon earlier studies by (1) demonstrating reduced peak VO2 and chronotropic incompetence much later after infection than other published studies, (2) also including evaluation of cardiac inflammation, structural heart disease and cardiovascular arrhythmias, (3) adjusting for likely confounders in our models, (4) including recovered persons as comparators, and (5) and demonstrating associations with higher inflammatory markers early in PASC. These studies, together with studies that included SARS-CoV-2 uninfected controls and casestudies without controls, have not reached consistent conclusions regarding patterns of reduced exercise capacity.…”
Section: Other Studies Of Pasc Using Cpetsupporting
confidence: 83%
See 3 more Smart Citations
“…Our study is consistent with six studies that have reported lower peak VO2 among those with PASC compared to recovered individuals at 3-6 months after COVID-19. [19][20][21][22][23][24] Our findings build upon earlier studies by (1) demonstrating reduced peak VO2 and chronotropic incompetence much later after infection than other published studies, (2) also including evaluation of cardiac inflammation, structural heart disease and cardiovascular arrhythmias, (3) adjusting for likely confounders in our models, (4) including recovered persons as comparators, and (5) and demonstrating associations with higher inflammatory markers early in PASC. These studies, together with studies that included SARS-CoV-2 uninfected controls and casestudies without controls, have not reached consistent conclusions regarding patterns of reduced exercise capacity.…”
Section: Other Studies Of Pasc Using Cpetsupporting
confidence: 83%
“…Two studies attributed lower peak VO 2 to inadequate augmentation of stroke volume 30 or chronotropic incompetence and poor stroke volume augmentation. 21 Others have attributed exercise limitations to ventilatory inefficiency from pulmonary vasculopathy, 18 respiratory abnormalities, 19 obesity and differences in cardiorespiratory fitness 29 and deconditioning. 20, 21…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conjuntamente, las indagaciones coinciden que el sexo femenino tiene mayor prevalencia de la enfermedad con un 63,6% (Augustin et al, 2021;Barbagelata et al, 2021). Por otro lado, Staub y Staub (2022) en su estudio manifiestan que el síndrome inflamatorio multisistémico (SIMS) está asociado al síndrome post COVID-19 detectado especialmente en menores de edad.…”
Section: Sintomatología Psicológicas Y Psiquiátricas Comunes Del Sínd...unclassified